The eternal pandemic. Analysis of Legislative Decree No. 1470 - Nava Flores, Jesús Marcelo (2021)
The state of emergency due to SARS-CoV-2 has meant a new challenge for protection measures in cases of violence against women. The rights to personal integrity and life of women need to be effectively adapted during the pandemic, as cases of violence increased due to the new advantages and stimulants for the aggressor to commit the crime. For this purpose, a conceptualization of human rights and violence against women in Peru will be made. Then, the law that regulates these measures and the decree under analysis will be delimited. Finally, it will be determined whether the proposed solutions address the rights at risk.